BRAMSBioBox: Developing an open research platform for audio and biosignals monitoring - van Vugt, Floris; Pintat, Valentin; Merrett, Dawn; Dalla Bella, Simone; Voix, Jérémie (Canadian Acoustics, 2023)
Over the recent years, researchers in various areas ranging from music neuroscience to cognitive psychology have been interested in understanding how music can be "embodied". To accelerate such research, a comprehensive hardware and software platform has been recently developed. Such platform, nicknamed "BRAMSBioBox", is featuring off-the-shelf electronic components and open-source data acquisition and synchronisation stacks. The current capabilities of the BRAMSBioBox will be demonstrated and illustrative research projects will be presented in various domains including non-musical ones.